Socialization of Increased Physical Fitness in the Covid Pandemic 19 Era - Arya T Candra; Moh. Agung Setiabudi; Mislan; Deni Kurniawan Efendi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2020)
Physical condition is the most important indicator in the life of every community to maximize daily physical activity. Physical condition is very closely related to physical fitness. One of the most effective ways to maintain one's physical fitness is to do physical activity or exercise regularly and continue. Physical activity that is carried out routinely is of course also able to increase body immunity or a person's resistance to a virus or disease, one of which is covid 19. The target of this community service activity is the community in Sumberberas Village, RW 04. The socialization activity to increase physical fitness began on the 18th July 19 2020, 09.00-12.00 WIB and located in the Al Munir mosque in the village of Sumberberas. Material related to physical activities delivered and recommended are jogging, cycling and aerobics by taking into account health protocols and physical distancing. On the first day in the implementation of this socialization activity there were 30 participants who participated and on the second day there were additional members of 20 people. So that the total participants of this socialization activity were 50 people. Based on the evaluation results it can be concluded that the participation of the people who took part in this socialization activity was classified as good and the community was also very enthusiastic.